The Nature of Guruship - Joseph Pdackal (Journal of Dharma, 1977)
Guruship is not only central but also common to most of the major religions and religious traditions of the world. Intense devotion to the Lord, and equal devotion to Guru are the essential preliminaries to the realization of the true path in Hinduism. Guru is sometimes regarded even as the incarnation of the deity. Among Sikhs, the term applies to the ten successive heads of their religion, the last of whom stopped the succession with himself declaring that henceforward the Sikh holy book, the Granth should be the Guru. This Guru Granth now receives almost divine homage. To the Christians Jesus Christ is the Guru who declared himself as "the way, truth and life". LS.P.C.K.’s recent publication. The Nature of ’ Guruship is an exhaustive study on the topic by various scholars.